HYGIENE AND SANITATION PRACTICES IN ANIMAL QURBAN SLAUGHTER IN FMD OUTBREAK - Rahmi, Annisa; Handarini, Ristika; Faqih, Ahmad; Mulyana, Dani; Kurniasih, Desta Dwi; Gagarin, Muhamad Yuri; Permadani Pertiwi, Pirda Parida; Gumelar, Restu; Baharun, Abdullah (Universitas Djuanda, 2022)
Hygiene and sanitation aspects are important requirement in slaughtering animals qurban at foot and mouth disease (FMD) outbreak situation in Indonesia. This community service aims to provide guarantees to the public that the meat from animals qurban by Djuanda University was ASUH (safe, health, intact, and halal), and doing the assessment for hygiene and sanitation apratices in slaughtering process. Antemortem and postmortem examinations conducted on 19 cows and 2 sheeps. Ante-mortem examination includes examination of general condition, age, body temperature, eyes mucosa, oral mucosa, and signs of disease. Postmortem examination carried on digestive tract organs, heart, lungs, liver, kidneys, spleen, head, and carcass. The application of hygiene and sanitation practices in slaughtering process were assessed with qualitatively assessment, 1 point for fulfilled and 0 for unfulfilled. Total points were summed and presented as a percentage. The results of postmortem examination show a case of fasciolosis in a cow’s liver, and 85% hygiene and sanitation aspects were fullfilled.